Proposal of Programming Practice to Promote Elaboration of Basic Knowledge on Cooking Basics for Elementary School Home Economics - 阪東 哲也; 岩崎 サオ里; 村田 晋太朗 (Educational Information Research, 2021)
The purpose of this study is to verify the effectiveness of educational practices that incorporate programming in the home economics of elementary schools and to obtain basic knowledge to improve elementary school programming education. The authors conducted a programming class for 33 fifth grader to promote elaboration of basic knowledge in “Cooking Basics”, a home economics course in elementary school, using Scratch, a visual programming language, and verified its educational effects. The results of the analysis indicated that engaging in learning activities that incorporate programming as a review of experiential learning leads to the elaboration of basic knowledge, and then to consolidation of subject learning. It was also suggested that it is possible to increase their interest in programming depending on the theme for both male and female students.